1994
DOI: 10.1136/ard.53.5.323
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis in patients with systemic sclerosis and severe digital ischaemia requiring amputation.

Abstract: Objectives-To document the incidence of histological vasculitis in amputation specimens from patients with severe digital ischaemia secondary to systemic sclerosis (SSc), and to look for an association between anticardiolipin (aCL) antibodies and severe digital ischaemia in SSc.Methods-This was a retrospective review of patients with SSc who underwent amputation for digital ischaemia over a three year period. Results-Five of nine patients had histological vasculitis, four of whom had aCL antibodies, although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 9 publications
0
31
2
Order By: Relevance
“…This may be in part because the subset of SSc patients with normotensive renal failure due to pANCA-positive crescentic GN has only been recognized more recently, since about 1994. Herrick et al 32 reported that 5 out of 9 patients with severe digital ischemia from SSc (all of the limited variant) had histologic evidence of vasculitis. In our current series of 15 cases, we found 6 had skin purpura, 2 had ischemic digital ulcers, 5 had mononeuritis multiplex and/or peripheral neuropathy, and 2 had myopathies.…”
Section: Discussionmentioning
confidence: 99%
“…This may be in part because the subset of SSc patients with normotensive renal failure due to pANCA-positive crescentic GN has only been recognized more recently, since about 1994. Herrick et al 32 reported that 5 out of 9 patients with severe digital ischemia from SSc (all of the limited variant) had histologic evidence of vasculitis. In our current series of 15 cases, we found 6 had skin purpura, 2 had ischemic digital ulcers, 5 had mononeuritis multiplex and/or peripheral neuropathy, and 2 had myopathies.…”
Section: Discussionmentioning
confidence: 99%
“…11 A single dose of aspirin usually results, however, in reversal of the ischemic phenomena with resolution of erythromelalgia in the vast majority of patients within 2 to 4 days. 2 Acute digital ischemia may be caused by several entities including collagen vascular diseases, 12 Raynaud's disease, 13 Buerger's disease, 14 peripheral atherosclerosis, 15 heparin-induced thrombocytopenia with thrombosis syndrome, 16 consumption coagulopathy, 17 and many others. Although rare, hematologic disorders, however, have to be considered in the differential diagnosis of acute digital ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Acute digital ischemia may be caused by several entities including collagen vascular diseases [3], Raynaud's disease [4], Buerger's disease [5], peripheral atherosclerosis [6], heparininduced thrombocytopenia with thrombosis syndrome [7], consumption coagulopathy [8] and many others. Although rare, hematologic disorders, however, have to be considered in the differential diagnosis of acute digital ischemia.…”
Section: Discussionmentioning
confidence: 99%